2015
DOI: 10.1107/s1399004715016892
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the GemC1 coiled coil and its interaction with the Geminin family of coiled-coil proteins

Abstract: GemC1, together with Idas and Geminin, an important regulator of DNA-replication licensing and differentiation decisions, constitute a superfamily sharing a homologous central coiled-coil domain. To better understand this family of proteins, the crystal structure of a GemC1 coiled-coil domain variant engineered for better solubility was determined to 2.2 Å resolution. GemC1 shows a less typical coiled coil compared with the Geminin homodimer and the Geminin–Idas heterodimer structures. It is also shown that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…Although these data suggest that GEMC1 acts upstream of Multicilin, it does not exclude the possibility that GEMC1 and Multicilin function together to promote MCC differentiation and potentially regulate MCC homeostasis. Consistent with this, the expression of both genes was reported to be specific to MCCs from single‐cell analysis of lung tissues (Treutlein et al , ) and we (Fig E) and others have observed an interaction between the 2 proteins that may impact their function, for example, by allowing a transition between EDG and EDM transcriptional complexes that could have distinct targets, functions or modes of regulation (Caillat et al , ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although these data suggest that GEMC1 acts upstream of Multicilin, it does not exclude the possibility that GEMC1 and Multicilin function together to promote MCC differentiation and potentially regulate MCC homeostasis. Consistent with this, the expression of both genes was reported to be specific to MCCs from single‐cell analysis of lung tissues (Treutlein et al , ) and we (Fig E) and others have observed an interaction between the 2 proteins that may impact their function, for example, by allowing a transition between EDG and EDM transcriptional complexes that could have distinct targets, functions or modes of regulation (Caillat et al , ).…”
Section: Discussionsupporting
confidence: 88%
“…As available data indicated that GEMC1, Multicilin and Geminin could interact through their CC domains, we next examined their relative influence on FOXJ1 activation (Caillat et al , , ). The co‐expression of Geminin with GEMC1 resulted in the near complete inhibition of FOXJ1 transcriptional activation (Fig C).…”
Section: Resultsmentioning
confidence: 99%
“…While Gemc1 and Mcidas are the major activators of MCC gene expression, Geminin suppresses this activity and thus inhibits MCC gene expression. This yin and yang of the Geminin‐Gemc1/Mcidas function appears to be a conserved feature, as Geminin is known as a negative regulator of DNA replication during cell cycle progression, whereas GemC1 and Mcidas are positive regulators of the process (Caillat et al , ).…”
Section: Geminin Family Members Within the MCC Gene Expression Programmentioning
confidence: 99%
“…34 All three members of Geminin superfamily regulate cell cycle progression and reveal similarity in their coiled-coil domain, while they interact with each other revealing high affinity in forming heretodimers. [1][2][3] Geminin is an inhibitor of pre-replicative complex formation, Mcidas regulates DNA replication and cell cycle progression through its binding to Geminin, while GemC1 mediates pre-initiation complex formation through its interactions with TopBP1 which results in the recruitment of Cdc45 and the initiation of replication. [1][2][3][4][5][6] Despite their role in DNA replication and cell cycle progression, all members of Geminin superfamily are involved on the regulation of cell fate decisions of stem cells.…”
mentioning
confidence: 99%
“…[1][2][3] Geminin is an inhibitor of pre-replicative complex formation, Mcidas regulates DNA replication and cell cycle progression through its binding to Geminin, while GemC1 mediates pre-initiation complex formation through its interactions with TopBP1 which results in the recruitment of Cdc45 and the initiation of replication. [1][2][3][4][5][6] Despite their role in DNA replication and cell cycle progression, all members of Geminin superfamily are involved on the regulation of cell fate decisions of stem cells. We and others have shown that Geminin controls self-renewal and fate commitment decisions, [7][8][9] in several populations of stem cells through interactions with chromatin remodelling/ modifying complexes, suggesting that Geminin is involved in a global epigenetic regulation of crucial transcription factors.…”
mentioning
confidence: 99%